JUMLAH WAKTU KEPALA PUSKESMAS UNTUK AKTIVITASADMINSTRASI DAN PROFESIONAL PUBLIC HEALTH DIKOTA DAN DESA(Analisis Data IFLS EAST 2012) - Veronika Suka; Mubasysyir Hasanbasri; Retna Siwi (Journal of Health Service Management, 2016)
Introduction: The public health service program outside the puskesmas building can be measured through severalindicators, namely health promotion, environmental health, maternal and child health, community nutrition and theeradication of infectious diseases. So far, outdoor research has focused more on promotional activities, communityempowerment and curative services. No one has examined managerial factors. therefore researchers are interested inconducting this research. Objective: To find out whether managerial factors can affect the out-of-building services of urban and rural health centers.Methods: This study is a quantitative study using secondary data from IFLS East 2012 with a cross sectional survey design.The population in this study is the head of the Puskesmas spread over 7 provinces in Eastern Indonesia. The total sampleof the study was 97 Heads of Puskesmas from IFLS East 2012 data spread across 7 provinces in Eastern Indonesia. namelyEast Nusa Tenggara, East Kalimantan, Southeast Sulawesi, Maluku, North Maluku, West Papua, and Papua. The method ofdetermining the 7 Provinces was based on Susenas data for July 2010. Results: Heads of non-doctor professional puskesmas in thevillage often conduct field activities outside the puskemas building than those who are doctors in cities. Field activitiessuch as posyandu and outreach were carried out 37 times more often by non-doctor heads of puskesmas in the village. Puskemas with a total number of medical personnel ? 15 people and located in rural areas, the head of the puskesmas often carries out field activities in the form of posyandu and counseling. Conclusion: Head of Puskesmas with a medical profession more often does activities outside the building for administrative activities such as meetings and seminars. The head of the puskesmas, who is not a doctor, often carries out activities outside the building, field visits in the form of counseling and posyandu. Puskesmas with a large number of staff often carry out field activities in the form of counseling and posyandu.Puskesmas located in rural locations have more outdoor activities than those in urban puskesmas.